Homogeneous Supermanifolds with Retract CP (1|4, k1k2 11) - M. A. Bashkin; L. I. Habadze (Моделирование и анализ информационных систем, 2007)
We give the results of classification of all nonsplit homogeneous supermanifolds over the complex projective line whose retract is corresponding to a holomorphic vector bundle with a set (k1, k2,1,1), where k1 >= k2 >= 1. See [3] and [4] for more information about the complex supermanifolds theory.